2019
DOI: 10.5812/jjhs.96788
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-Analysis of the Bed Bug Infestation (Cimex lectularius) as a Public Health Insect in Iran (1995 – 2019)

Abstract: Background:The common bed bug (Cimex lectularius) is a small hematophagous and wingless insect of the order of Hemiptera and the Cimex genus. This insect is mainly nocturnal and feeds specifically on humans. Objectives: This systematic review reflects the distribution of the bed bug and this is a hypothesis about the relationship between the mean of humidity and temperature with the bed bug infestation that the meta-analysis evaluates. Data Sources: Various electronic databases were investigated for choosing r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The presence of bed bugs has been documented in Kashan (6.7%). A meta-analysis study of the bed bug infestation (Cimex lectularius) in Iran during 1995-2019 reported the weighted mean of this infestation was estimated 0.28 (18). A door-to-door survey showed 11.1% of Cimex lectularius infestations in row homes in Philadelphia, Pennsylvania (19).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of bed bugs has been documented in Kashan (6.7%). A meta-analysis study of the bed bug infestation (Cimex lectularius) in Iran during 1995-2019 reported the weighted mean of this infestation was estimated 0.28 (18). A door-to-door survey showed 11.1% of Cimex lectularius infestations in row homes in Philadelphia, Pennsylvania (19).…”
Section: Discussionmentioning
confidence: 99%
“…Bed bugs are human ectoparasites that include two species Cimex lectularius and Cimex hemipterus [3]. Recently, bed bugs infestation has been increased globally [4] and it has become a major concern to public health [5] and economic importance [6]. Hence, some pest professionals in the U.S. have reported these pests as the most challenging pest to control [5,7].…”
Section: Introductionmentioning
confidence: 99%